(untitled) - Fusetsu-gaki, Tôsen (Singapore, 1998)
This book offers straightforward ... excellent translations of a rare set of Japanese records with limited, although helpful, explanations and notes dealing mainly with matters of Southeast Asian interest
Keywords: Southeast Asia,Đông Nam Á; Commerce,History,Thương mại,Lịch sử